Uniaxially aligned electrospun fibers for advanced nanocomposites based on a model PVOH-epoxy system. (February 2016) - Karimi, Samaneh; Staiger, Mark P.; Buunk, Neil; Fessard, Alison; Tucker, Nick
Abstract: This work demonstrates the potential of aligned electrospun fibers as the sole reinforcement in nanocomposite materials. Poly(vinyl alcohol) and epoxy resin were selected as a model system and the effect of electrospun fiber loading on polymer properties was examined in conjunction with two manufacturing methods. A proprietary electrospinning technology for production of uniaxially aligned electrospun fiber arrays was used. A conventional wet lay-up fabrication method is compared against a novel, hybrid electrospinning–electrospraying approach. The structure and thermomechanical properties of resulting composite materials were examined using scanning electron microscopy, dynamic mechanical analysis, thermogravimetric analysis, differential scanning calorimetry, Fourier transform infrared spectroscopy, and tensile testing. The results demonstrate that using aligned electrospun fibers significantly enhances material properties compared to unreinforced resin, especially when manufactured using the hybrid electrospinning–electrospraying method. For example, tensile strength of such a material containing only 0.13 vol% of fiber was increased by ∼700%, and Young's modulus by ∼250%, with concomitant increase in ductility.